One-Pot Synthesis of 1,2,3-Triazole-Fused Polycyclic Systems via Sequential Annulation of 1,n-Enynes with Tosyl Azide - Zhou, Ting; Yang, Liangliang; Lang, Ming; Peng, Shiyong (Synthesis, 2022)
An efficient one-pot sequential annulation of 1,n-enynes with tosyl azide is reported, providing a series of novel N-alkyl 1,2,3-triazole-fused polycyclic scaffolds in moderate to excellent yields under mild reaction conditions.
Keywords: 1,n-enyne; tosyl azide; fused 1,2,3-triazole; one-pot reaction; cyclization